Properties of terrestrial gamma ray flashes detected by AGILE MCAL below 30 MeV. Issue 2 (20th February 2014) - Marisaldi, M.; Fuschino, F.; Tavani, M.; Dietrich, S.; Price, C.; Galli, M.; Pittori, C.; Verrecchia, F.; Mereghetti, S.; Cattaneo, P. W.; Colafrancesco, S.; Argan, A.; et al.
<x xml:space="preserve">Abstract</x> We present the characteristics of 308 terrestrial gamma ray flashes (TGFs) detected by the Minicalorimeter (MCAL) instrument on board the AGILE satellite during the period March 2009–July 2012 in the ±2.5° latitude band and selected to have the maximum photon energy up to 30 MeV. The characteristics of the AGILE events are analyzed and compared to the observational framework established by the two other currently active missions capable of detecting TGFs from space, RHESSI and Fermi. A detailed model of the MCAL dead time is presented, which is fundamental to properly interpret our observations. The most significant contribution to dead time is due to the anticoincidence shield in its current configuration and not to the MCAL detector itself. Longitude and local time distributions are compatible with previous observations, while the duration distribution is biased toward longer values because of dead time. The intensity distribution is compatible with previous observations, when dead time is taken into account. The TGFs cumulative spectrum supports a low production altitude, in agreement with previous measurements. We also compare our sample to lightning sferics detected by the World Wide Lightning Location Network and suggest a new method to assess quantitatively the consistency of two TGF populations based on the comparison of the associated lightning activity. According to this method, AGILE and RHESSI samples are compatible with the same parent population. The AGILE TGF catalog below 30 MeV is accessible online at the website of the ASI Science Data Center http://www.asdc.asi.it/mcaltgfcat/.